The physics and regularities of the neutron-thermoacoustic instability - S. N. Pelykh; Huiyu Zhou; O. B. Maksymova (Ядерна фізика та енергетика)
The physics and regularities of the neutron-thermoacoustic instability (NTAI) in nuclear channels with subcooled nucleate boiling flows are explained. The method for obtaining the characteristic equation of NTAI in a VVER-type reactor is given. The influence of steam reactivity coefficient ∂k/∂φ on NTAI boundaries is studied and the effect of a negative ∂k/∂φ favouring the oscillatory instability of neutron flux and pressure is shown.